Calcaneal distraction vs. cast immobilization for the preoperative treatment of patients with Danis–Weber type C ankle fractures: a case–control study - Song, Bing; Shi, Jisheng; Xu, Xiaohui; Hou, Xiangfeng; Jia, Jingkun; Pang, Tongtao (Frontiers in Surgery, 2024)
Ankle fractures require temporary fixation to allow swelling to subside prior to surgery; this is typically achieved using calcaneal distraction or cast immobilization. We compared the results of these methods in the treatment of Danis-Weber type C ankle fractures. Methods: This retrospective study analyzed the data of 86 patients with Danis-Weber type C ankle fractures, of whom 40 underwent calcaneal distraction and 46 underwent cast immobilization. Clinical measures including preoperative detumescence time, daily swelling value, skin condition, and pain, SF-36 Health Survey (SF-36) score and ankle scores were compared between the two groups. Results: Baseline characteristics did not differ significantly between the groups. Calcaneal distraction resulted in a lower preoperative detumescence time (6.22±0.64 vs. 8.94±0.82 days) and lower daily swelling values compared with cast immobilization, leading to a lower skin necrosis rate. Resting pain scores were significantly lower in the calcaneal distraction group than in the cast immobilization group at various postoperative time points (P<0.05). Ankle function scores were higher in the calcaneal distraction group than in the cast immobilization group at 12 months postoperatively (P<0.05), indicating improved outcomes. Additionally, the SF-36 quality of life scores of patients undergoing calcaneal distraction were notably superior to those in the cast immobilization group. Discussion: Calcaneal distraction is superior to cast immobilization in reducing soft tissue swelling, alleviating pain, and enhancing ankle function recovery in patients with Danis-Weber type C ankle fractures. Early calcaneal distraction upon hospital admission is recommended to optimize surgical outcomes.